(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Polyarchy, as a distinct category in the theory of forms of government, is inclusive of the role plaid by acts, facts and actors other the ones considered in established categories of forms of government. The hypothesis appears to be confirmed and verified through an analysis of some factors of resilience to the case law in Dobbs. Such factors are referenda that have been voted in some states (California, Kansas, Kentucky, Michigan, Vermont and, indirectly, Montana) and have achieved giving constitutional status to reproductive rights; as well as some post Dobbs case law by some state Supreme Courts (Indiana and South Carolina, not in Idaho).